A Decade of Th9 Cells: Role of Th9 Cells in Inflammatory Bowel Disease - Vyas, Shachi Pranjal; Goswami, Ritobrata (Frontiers in Immunology, 2018)
T helper cell subsets play a critical role in providing protection against offending pathogens by secreting specific cytokines. However, unrestrained T helper cell responses can promote chronic inflammation-mediated inflammatory diseases. Dysregulated T helper cell responses have been suggested to be involved in the pathogenesis of multiple inflammatory diseases, including allergic airway inflammation, rheumatoid arthritis, and inflammatory bowel disease (IBD) among others. Aberrant pro-inflammatory responses induced by Th1, Th2, and Th17 subsets are known to trigger IBD. IBD is a chronic inflammatory disease characterized by weight loss, diarrhea, pain, fever, and rectal bleeding. It poses a major health burden worldwide owing to the increased risk of colorectal cancer development. Despite numerous therapeutic advancements, IBD still remains a major health burden due to the inefficiency of the conventional therapies. Recently, IL-9-secreting Th9 cells are known to be involved in the pathogenesis of IBD. However, the role of Th9 cells and their secretory cytokine IL-9 in IBD is unclear. The functional relevance of Th9 cells is also relatively understudied in IBD. Thus, investigating the actual role of various T helper cell subsets including Th9 cells in IBD is essential to develop novel therapies to treat IBD. Here, we highlight the role of Th9 cells in promoting IBD. We discuss the mechanisms that might be employed by Th9 cells and IL-9 in promoting IBD and thereby propose potential targets for the treatment of Th9 cell-mediated IBD.